2012
DOI: 10.1142/s0219477512500149
|View full text |Cite
|
Sign up to set email alerts
|

On the Separability Between Signal and Noise in Singular Spectrum Analysis

Abstract: Communicated by Zoltan GinglThe optimal value of the window length in singular spectrum analysis (SSA) is considered with respect to the concept of separability between signal and noise component, from the theoretical and practical perspective. The theoretical results confirm that for a wide class of time series of length N , the suitable value of this parameter is median {1, . . . , N}. The results of both simulated and real data verify the effectiveness of the theoretical results. The theoretical results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…results and studies based on a wide class of simulated and real data which indicate that the optimal choice of the embedding dimension or window length is close to one half of the time series length [15,16]. The number of noise surrogates used in MCSSA was 1000.…”
Section: Resultsmentioning
confidence: 99%
“…results and studies based on a wide class of simulated and real data which indicate that the optimal choice of the embedding dimension or window length is close to one half of the time series length [15,16]. The number of noise surrogates used in MCSSA was 1000.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the behavior of the singular values and the w-correlations (a definition of the w-correlation can be found in Golyandina et al, 2001) among components within each dataset, we consider r = 13, r = 6, and r = 17, for the USAc-cDeaths, UKgas and AirPassengers, respectively. It is worth mentioning that USAccDeaths series was previously studied in Hassani (2007) and Hassani et al (2012), and they found that the above parameters are optimal in the sense that they produce acceptable forecasts.…”
Section: Real Datamentioning
confidence: 98%
“…As explained in Hassani et al (2012), if the absolute value of the wcorrelations is small, then the corresponding series are almost w-orthogonal, but, if it is large, then the two series are far from being w-orthogonal and are therefore badly separable. As an example, we present in Figure 2 the wcorrelation matrix for the United States to show the dependence between signal and noise components.…”
Section: Evaluating the Mfmssa Approachmentioning
confidence: 99%